Leahey, Whitewashing War - Historical Myth, Corporate Textbooks, And Possibilities For Democratic Education - Schwarz, Marc (Teaching History: A Journal of Methods, 2010)
No one who reads this study will have any difficulty identifying its thesis. The reader discovers it at the outset of the book and the author sustains it constantly to the end. In fact, Leahey presents his conclusion at the very beginning, giving the appearance of both a polemical and one-sided investigation. Whitewashing War asserts that public social studies education in American schools is influenced and controlled by forces such as the government, the military, the industrial establishment, and the media. Through federal action, military involvement, textbook sanitization, and media omissions the effort is to indoctrinate students with patriotism and loyalty, thus insuring a passive, obedient response. While this point of view is not without merit, in its ideological presentation it savors too much of a dictum rather than a matter for discussion.